2014
DOI: 10.1007/s00441-014-1906-9
|View full text |Cite
|
Sign up to set email alerts
|

The cell–cell junctions of mammalian testes: I. The adhering junctions of the seminiferous epithelium represent special differentiation structures

Abstract: The seminiferous tubules and the excurrent ducts of the mammalian testis are physiologically separated from the mesenchymal tissues and the blood and lymph system by a special structural barrier to paracellular translocations of molecules and particles: the “blood–testis barrier”, formed by junctions connecting Sertoli cells with each other and with spermatogonial cells. In combined biochemical as well as light and electron microscopical studies we systematically determine the molecules located in the adhering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 108 publications
2
28
0
1
Order By: Relevance
“…Additionally, it was recently demonstrated that mitochondrial ROS generation could trigger autophagy , leading to the accumulation of damaged mitochondria and enhanced ROS production. All the above processes negatively affect blood–testis barrier (BTB) integrity, contributing to distorted spermatogenesis , , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was recently demonstrated that mitochondrial ROS generation could trigger autophagy , leading to the accumulation of damaged mitochondria and enhanced ROS production. All the above processes negatively affect blood–testis barrier (BTB) integrity, contributing to distorted spermatogenesis , , …”
Section: Discussionmentioning
confidence: 99%
“…All the above processes negatively affect blood-testis barrier (BTB) integrity, contributing to distorted spermatogenesis. 42,43,44 On this basis, the primary objective of the present study was to evaluate redox balance in patients with azoospermia, in order to establish the potential role exerted by ROS in the genesis of testicular secretory injury, when NOA occurs. optimize the better therapeutic approach and to counsel properly the infertile patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine tissue samples of freshly slaughtered animals were obtained in the regional slaughterhouse (Mannheim, Germany), murine tissue samples (rat and mouse), and guinea pig tissues from mature and sexually active animals kept in the Central Animal Laboratory of the German Cancer Research Center (Heidelberg, Germany; for details see Franke et al 2006Franke et al , 2015Domke et al 2014). Tissue specimens from 3-year-old boars (German landrace pigs) were provided by Dr. Heiner Niemann, head of the Institute of Farm Animal Genetics (Friedrich-Loeffler-Institute, Federal Research Institute for Animal Health, Mariensee, Germany) and fixed as described (Rickelt et al 2011;Domke et al 2014). Human tissue samples were obtained from surgical material taken and processed in compliance with the regulations of the Ethics Committees of the Universities of Heidelberg and Marburg (Germany; see also Franke et al 2006Franke et al , 2015Domke et al 2014).…”
Section: Tissues and Cellsmentioning
confidence: 99%
“…In previous studies of mature mammalian testes, we had noted that the epithelium within the seminiferous tubules is fundamentally different from all other epithelia, including those of the testicular excurrent ducts. With respect to the major molecular and ultrastructural components in the mature and healthy seminiferous tubules, it has for example been found that in this stage, the Sertoli and germ cells do not contain any cytokeratin (CK) but only vimentin intermediate-sized filaments (IFs), often organized in bundles enriched in the perinuclear region (Franke et al 1979(Franke et al , 1982b; see also Spruill et al 1983;Paranko and Virtanen 1986; for further references, see Domke et al 2014); do not contain desmosomes or desmosome-like structures, not even any desmosome-specific marker proteins or glycoproteins (Franke et al 1982a;Domke et al 2014; for a list of opposite reports and claims, see ESM, Table S1); do not contain E-cadherin (CDH1)-based but only Ncadherin (CDH2)-based adherens junctions (AJs; Franke et al 1982a;Cyr et al 1992Cyr et al , 1993Newton et al 1993;Byers et al 1994;Domke et al 2014;Domke 2018); and do not contain an apical zonula adhaerens but deep plasma membrane indentations in the apical plasma membranes of the Sertoli cells in which the spermatid heads are embedded (cf. Franke et al 1978a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation